Znaczenie determinacji w nauce języka angielskiego jako obcego na poziomie zaawansowanym - Pawlak, Mirosław; Zawodniak, Joanna; Kruk, Mariusz (Neofilolog, 2021)
Second language acquisition (SLA) researchers have long been engaged in investigating the effect of a range of learner individual differences (IDs, e.g., motivation, anxiety and aptitude) on L2 learning and achievement. At the same time, there are no more than a few studies focusing of on learner personality and its place in SLA and the relationship between personality traits and other ID variables. One such underappreciated and thus poorly recognized personality trait is grit, understood as a combination of perseverance and passion for long-term goals. The present paper reports a study in which grit was investigated among advanced university students majoring in English with the help of a language-specific grit scale and semi-structured interviews. The empirical considerations are preceded by a small number of theoretical comments on the nature of grit and related research that was conducted to date. The paper ends with the discussion of future research directions and possible pedagogical implications.